2020
DOI: 10.1136/bjophthalmol-2020-316149
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of therapies for the corneal endothelium: past, present and future approaches

Abstract: Corneal endothelial diseases are leading indications for corneal transplantations. With significant advancement in medical science and surgical techniques, corneal transplant surgeries are now increasingly effective at restoring vision in patients with corneal diseases. In the last 15 years, the introduction of endothelial keratoplasty (EK) procedures, where diseased corneal endothelium (CE) are selectively replaced, has significantly transformed the field of corneal transplantation. Compared to traditional pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 219 publications
1
61
0
2
Order By: Relevance
“…The availability of various treatment modalities is clinically significant, as each is more or less appropriate for different circumstances. Imaging techniques can potentially enable the individual chances of success of each therapy to be evaluated [28]. It appears that in the medium term the work of cornea banks is becoming more complex and will require a higher degree of specialisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of various treatment modalities is clinically significant, as each is more or less appropriate for different circumstances. Imaging techniques can potentially enable the individual chances of success of each therapy to be evaluated [28]. It appears that in the medium term the work of cornea banks is becoming more complex and will require a higher degree of specialisation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most corneal transplants in Germany are posterior lamellar keratoplasties for diseases of the corneal endothelium [27], and, as such, this article outlines some examples of developments in replacing diseased corneal endothelia. One alternative to endothelial keratoplasty (for instance, Descemet membrane endothelial keratoplasty (DMEK)) is the use of cultured corneal endothelial cells, which are injected as a suspension into the anterior chamber [28,29]. After injection, the recipient must remain in a prone position for a few hours.…”
Section: Cell Therapy and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…9 Another limitation of the cadaveric donor transplantation is the long-term risk of allogenic graft rejection and failure. 18 Transplant failure is often due to loss of hCECs from the donor layer. It has been reported that 30% of hCECs are lost within the first 6 months of transplantation.…”
Section: New Approaches To Corneal Endothelial Replacementmentioning
confidence: 99%
“…Novel, alternative treatments based on regenerative medicine and cell-based therapies are being developed for FECD. 14 For example, tissue-sparing surgical approaches, such as Descemet-stripping only (DSO), eliminate the need for transplanted endothelial replacement and provide an alternative strategy without the use of donor tissue. 15 Given the gap since previous assessments and the availability of new treatment options, an up-to-date robust assessment of the cost of transplant surgery can provide benchmark information to evaluate the cost-effectiveness of new-generation FECD treatments.…”
Section: Introductionmentioning
confidence: 99%